Synthesis of PVP-functionalized ultra-small MoS2 nanoparticles with intrinsic peroxidase-like activity for H2O2 and glucose detection. Issue 84 (26th August 2016) - Yu, Jie; Ma, Xiaoyan; Yin, Wenyan; Gu, Zhanjun
Abstract : PVP-MoS2 NPs with ultra-small size were synthesized and had good biocompatibility and good environmental tolerance. A low cost, facile colorimetric sensor based on their high peroxidase-like catalytic efficiency was used to detect H2 O2 and glucose. Abstract : Polyvinylpyrrolidone (PVP)-modified MoS2 nanoparticles (PVP-MoS2 NPs) with d = 5 nm and in high purity and yield were prepared by a facile one-pot hydrothermal method. Cytotoxicity and hemolysis studies demonstrated that PVP-MoS2 NPs show good biocompatibility. The PVP-MoS2 NPs exhibited remarkable peroxidase-like catalytic activity, which was similar to that of horseradish peroxidase (HRP). Based on this peroxidase-like activity, a platform for colorimetric detection of H2 O2 was established. We have found that these NPs have high sensitivity to detect H2 O2 with a nearly linear range between 2.0 × 10 −6 mol L −1 and 1.5 × 10 −4 mol L −1 . Furthermore, the PVP-MoS2 NPs were also used for glucose measurement in serum by quantifying the released H2 O2 in the presence of glucose oxidase. The linear range for glucose detection was from 1.0 × 10 −3 mol L −1 to 1.0 × 10 −2 mol L −1 . This work will pave a way for the high-throughput synthesis of other ultra-small transition metal dichalcogenide (TMDs) NPs. Such enzyme-mimic nanomaterials could be a useful tool for medical diagnosis.